Glucose metabolism of visceral adipose tissue measured by (18)F-FDG PET/CT is related to the presence of colonic adenoma - Yoon, Hai-Jeon (Medicine (Baltimore), 2017)
This study investigated the relationships between the area and metabolic activity of adipose tissue and the presence of colorectal adenoma (CRA). Our institutional review board approved the study and waived informed consent. A total of 212 subjects who underwent fluorine 18 fluorodeoxyglucose (FDG) positron emission tomography (PET)/computed tomography (CT) and colonoscopy for routine health check-ups were enrolled. The volumetric parameters of areas of visceral (VAT(av)), subcutaneous (SAT(av)), and total adipose tissue (TAT(av)) and calculated visceral-to-subcutaneous adipose tissue ratio (VSR) and visceral-to-total adipose tissue ratio (VAR) were considered. Metabolic parameters of standardized uptake value (SUV) of visceral ((vc)SUV(max), (vc)SUV(mean)), subcutaneous ((sc)SUV(max), (sc)SUV(mean)), and calculated visceral-to-subcutaneous adipose tissue ratio (VSR(max), VSR(mean)) were considered. Anthropometric data of height, weight, body mass index (BMI), waist circumference (WC), body fat mass (BFM), skeletal muscle mass (SMM), and diverse laboratory data were also considered as variables. Sixty-six subjects were placed in the CRA group and 146 subjects in the non-CRA group. The presence of CRA was significantly correlated with older age (P  =  .001), male sex (P  =  .041), higher BMI (P  =  .004), higher WC (P  =  .001), higher BFM (P  =  .024), higher VAT(av) (P < .001), higher TAT(av) (P  =  .004), higher VSR (P < .001), higher VAR (P < .001), lower (vc)SUV(max) (P  =  .002), lower (vc)SUV(mean) (P < .001), and lower VSR(mean) (P  =  .002). On multiple regression analysis, (vc)SUV(max) and (vc)SUV(mean) were independently associated with the presence of CRA (P  =  .009 and P  =  .045). Lower glucose metabolism of visceral adipose tissue was related to the presence of CRA. Our findings identify the value of visceral metabolic dysfunction as a potential surrogate marker of elevated risk for CRA.